Exile and embrace: contemporary religious discourse on the death penalty - Santoro, Anthony (Northeastern University Press, 2013)
Examining the religious debates and dimensions of the death penalty in America
Description based upon print version of record
Keywords: Electronic books; Hochschulschrift; Todesstrafe; Religion; USA